Determinants of the price response to residential water tariffs: Meta-analysis and beyond. (March 2018) - Marzano, Riccardo; Rougé, Charles; Garrone, Paola; Grilli, Luca; Harou, Julien J.; Pulido-Velazquez, Manuel
Abstract: Meta-analyses synthesise available data on a phenomenon to get a broader understanding of its determinants. This work proposes a two-step methodology. 1) Based on a broad dataset of residential water demand studies, it builds a meta-regression model to estimate mean and standard deviation of price elasticity of residential water demand. 2) The resulting meta-model serves as a basis for implementing an approach that directly simulates the range of price elasticities resulting from policy-relevant combinations of its determinants. This simulation approach is validated using the available dataset. Despite evidence of low average price elasticity, the scenarios simulated using our meta-regression estimates show that increasing block rate tariffs are associated with higher price elasticity, and stresses the importance of using state-of-the-art methodologies when evaluating the price response. This completes other methodological insights obtained from the meta-analysis itself. Policy implications on the use of pricing to bring about water savings are discussed. Highlights: Meta-analysis of residential water price elasticity from largest database yet. Resulting statistical model used to formulate a simulation approach. Approach validated using available dataset. Approach can give a primary estimate of the efficiency of new pricing policies. Approach shows the impact of tariff structure and estimation methodology.